Organoleptic Test of Herbal Drinks From Family Medicinal Plants as Body Immunity in The Covid-19 Pandemic - Muhammad Siddik Sinaga; Inayah Rizki Khaesarani; Sonya Liani Nasution; Jumatun Riskinandiya; Eliska Eliska (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2021)
Family Medicinal Plants (FMP) have benefits and properties for the health of the body. However, this plant is only used as a kitchen spice alone without knowing other properties. Thus, then created an innovation or new product from the family medicinal plant. The goal is to find out the benefits of herbal beverage products through Organoleptic tests as the body's immunity during the Covid-19 pandemic for the people of Pulau Sejuk Village. This product is called Jakusema Herbal, which consists of ginger, turmeric, lemongrass, and honey. The research design uses a Pre-Experimental Design type One-Shot Case Study with nine panellists as research subjects. The study parameters used organoleptic and qualitative tests of vitamin C with potassium iodine (betadine) to see whether or not vitamin C was present in herbal beverage products. The results showed the best treatment was P2 treatment with consumer-preferred levels reaching: (1) colour 7,055>6,23 (2) texture 9,475>6,23, (3) taste 28,003>6,23, and (4) scent 7,617>6,23. Based on the results of organoleptic tests obtained that P2 treatment has a real influence on herbal beverage products. Furthermore, herbal beverage products were tested qualitatively. Then, P2 treatment has a higher vitamin C content than other treatments seen from discolouration in the product. Due to time constraints, vitamin C testing is only done qualitatively. It is recommended for further research using quantitative tests so that the data of research results are more detailed and accurate.